Identification of a Novel Parallel β-Strand Conformation within Molecular Monolayer of Amyloid Peptide - Liu, Lei (2017)
The differentiation of protein properties and biological functions arises from the variation in the primary and secondary structure. Specifically, in abnormal assemblies of protein, such as amyloid peptide, the secondary structure is closely correlated with the stable ensemble and the cytotoxicity. In this work, the early Aβ33-42 aggregates forming the molecular monolayer at hydrophobic interface are investigated. The molecular monolayer of amyloid peptide Aβ33-42 consisting of novel parallel β-strand-like structure is further revealed by means of a quantitative nanomechanical spectroscopy technique with force controlled in pico-Newton range, combining with molecular dynamic simulation. The identified parallel β-strand-like structure of molecular monolayer is distinct from the antiparallel β-strand structure of Aβ33-42 amyloid fibril. This finding enriches the molecular structures of amyloid peptide aggregation, which could be closely related to the pathogenesis of amyloid disease.